SOSIALISASI DAN EDUKASI MITIGASI BENCANA GEMPA BUMI DI WILAYAH KERJA PUSKESMAS JAJAWAY KOTA BANDUNG - Trisno Subekti; Suparni Suparni; Usan Daryaman (LPPM Universitas Abdurrab, 2025)
Earthquake faults are faults that can cause earthquakes due to the movement/friction of the fault itself. The Lembang Fault is a fault that stretches along 29 kilometres from Ngamprah Padalarang, West Bandung Regency to Palintang Pasirwangi Ujung Berung, Bandung City. Based on information, the Lembang Fault experienced the last earthquake in the 15th century or about 500 years ago, but that does not mean that this fault is not active based on the results of research by scientists from the National Innovation Research Agency (BRIN), the Lembang Fault always moves as much as 3 mm to 5 mm every year, this figure is included in the category of small movements. The implementation methods applied in this activity are: 1) community-based, 2) comprehensive, 3) Participatory, 4) quantitative approach. Through the community service program held by the Dharma Husada College of Health Sciences, the implementation team conducted socialisation and education on earthquake disaster mitigation in the working area of Puskesmas Jajaway, Bandung City. The output of this activity is that the surrounding community in particular gains knowledge and additional abilities to be able to carry out simple analyses of disaster risk in the area around them, namely Earthquake. Community participation was very high in this activity, this can be seen from the large attendance in this socialisation and education activity. In addition, the knowledge of the community who participated in the socialisation and education has increased, so it is only natural that this activity can be carried out regularly.